TO EVALUATE THE EFFICACY OF GUDUCHYADI YOGA IN THE MANAGEMENT OF RAKTACHAPADHIKYATA OR ESSENTIAL HYPERTENSION-A RANDOMIZED CONTROLLED CLINICAL TRIAL (International Journal of Ayurveda and Pharma Research, 2020)
Hypertension is the most pressing public health challenges. It is estimated that approximately 1 billion people are suffering from high blood pressure and the numbers are to increase to 2.5 billion by 2025. Raktachaapadhikya is the coined term for increased blood pressure given by recent authors where it can be understood as the pathology of Vyanvayu. The usage of Guduchyadi Yoga has been highlighted in the classics of Ayurveda for targeting the Hridaya sthitha vayu, which has not been evaluated yet. Aim: To evaluate and compare the efficacy of Navahridaya Kalpa (standard drug) and Guduchyadi Yoga (trial drug) for management of essential hypertension. Materials and Methods: A simple randomized controlled clinical study where 40 patients were equally divided as group A: Navahridaya kalpa (standard drug) and Group B: Guduchyadi yoga (trial drug) for a period of one month. Observations and results: The study result revealed that both the groups were beneficial in reducing high blood pressure however with no statistically significant difference found between the groups with p value being 0.339 for standard drug and 0.363 for trial drug. The group B was also found to be effective in reducing systolic blood pressure of stage I hypertension with p value .044 on comparing between the groups. Conclusion: The Guduchyadi yoga acts as Rasayana with the property of rejuvenation and antihypertensive which will check the high blood pressure at a very minimum cost without having any major adverse effects in the patients and hence can be advocated for use on a daily a basis.